2014
DOI: 10.4049/jimmunol.1302883
|View full text |Cite
|
Sign up to set email alerts
|

KIR3DL01 Recognition of Bw4 Ligands in the Rhesus Macaque: Maintenance of Bw4 Specificity since the Divergence of Apes and Old World Monkeys

Abstract: The identification of MHC class I ligands for rhesus macaque KIRs is fundamental to our basic understanding of KIR and MHC class I co-evolution and to the study of NK cell responses in this non-human primate model for AIDS and other viral diseases. Here we show that Mamu-KIR3DL01, which is expressed by approximately 90% of rhesus macaques, recognizes MHC class I molecules with a Bw4 motif. Primary NK cells expressing Mamu-KIR3DL01 were identified by staining with a mAb herein shown to bind Mamu-KIR3DL01 alloty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 52 publications
3
58
0
Order By: Relevance
“…In comparison to human inhibitory KIR (iKIR), the iKIR–MHC class I interactions in macaques are characterized by lower avidity and broader reactivity . Although the Bw4/Bw6 motifs play a role in binding macaque KIR3D proteins, there are some KIR3D with restricted specificity for Bw4 such as KIR3DL01 or KIR3DLW03, whereas other iKIR bind to both motifs such as KIR3DL05 or KIR049‐4 . One reason for this broader reactivity of some iKIR might be the enormous genetic diversity and copy number variation in macaque species that might favour the evolution of KIR with broad interaction specificity.…”
Section: The Kir and Mhc Class I Gene Families Of Macaquesmentioning
confidence: 99%
“…In comparison to human inhibitory KIR (iKIR), the iKIR–MHC class I interactions in macaques are characterized by lower avidity and broader reactivity . Although the Bw4/Bw6 motifs play a role in binding macaque KIR3D proteins, there are some KIR3D with restricted specificity for Bw4 such as KIR3DL01 or KIR3DLW03, whereas other iKIR bind to both motifs such as KIR3DL05 or KIR049‐4 . One reason for this broader reactivity of some iKIR might be the enormous genetic diversity and copy number variation in macaque species that might favour the evolution of KIR with broad interaction specificity.…”
Section: The Kir and Mhc Class I Gene Families Of Macaquesmentioning
confidence: 99%
“…Although rhesus KIR3DL01 and human KIR3DL1 are not orthologous, they may have similar functions; both recognize Bw4 ligands and are the most polymorphic KIRs of their respective species [29]. Moreover, the lysis of HIV-infected cells by KIR3DL1 + NK cells is primarily triggered by downmodulation of HLA-Bw4 ligands from the cell surface by the viral Nef protein [8,22], and we previously demonstrated that Mamu-Bw4 molecules are efficiently downmodulated by SIV Nef [65].…”
Section: Discussionmentioning
confidence: 99%
“…Glu76 has also been shown to play a role in regulating KIR interactions with the Bw4 motif in non-human primates (39). Interestingly, in contrast to human KIR3DL1*001, recognition of Bw4 allotypes by Mamu-KIR3DL01 was impaired by the presence of a glutamate at position 76.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in contrast to human KIR3DL1*001, recognition of Bw4 allotypes by Mamu-KIR3DL01 was impaired by the presence of a glutamate at position 76. Indeed ligands for Mamu-KIR3DL01 such as Mamu-B*65:01, have a glycine at this position and mutation to glutamate impaired recognition (39). It is nevertheless unclear whether this inability to tolerate a glutamate at position 76 stems from an altered positioning of the side chain relative to human Bw4 allotypes or that the mode of ligand recognition differs between Mamu-KIR3DL01 and KIR3DL1*001.…”
Section: Discussionmentioning
confidence: 99%